NAVIGATING ETHICAL LONG-TERM PERSONAL DATA STORAGE: PRIVACY, SECURITY, REGULATORY CHALLENGES, AND SOCIETAL IMPACT REVIEW - Adedokun, Simeon Ayoade; Adedokun, Theophilus Adedayo (Jurnal Techno Nusa Mandiri, 2025)
Digital data storage is now fundamental to modern society, facilitating the collection and utilization of vast information resources. Yet, the exponential growth of stored data has intensified ethical concerns, particularly regarding long-term retention. This multidisciplinary review synthesizes literature on the ethical implications of long-term data storage, focusing on privacy, security, data ownership, accessibility, sustainability, and societal impact. The study analyzes ethical frameworks encompassing deontology, privacy by design, fair information practices, data minimization, and accountability while examining the responsibilities of organizations, individuals, regulators, technology providers, and ethics committees in upholding ethical standards. Key findings reveal that the ethical landscape of long-term data storage is highly complex and demands a collaborative, multi-stakeholder approach. The review concludes by recommending the integration of robust security measures, enhanced user control and consent mechanisms, sustainable storage technologies, and governance frameworks prioritizing fairness, non-discrimination, and the public good. These recommendations aim to guide stakeholders toward responsible and ethical data stewardship, ensuring that digital data storage practices remain trustworthy and sustainable amid ongoing technological and societal change